Fraction of spectral solar radiance transmitted through snow and sea ice as measured in different depths under sea ice (transflectance) at station PS122/3_37-20 on 2020-04-21, survey 2, version 2.0 - Anhaus, Philipp; Arndt, Stefanie; Katlein, Christian; Krampe, Daniela; Lange, Benjamin Allen; Matero, Ilkka; Regnery, Julia; Rohde, Jan; Schiller, Martin; Nicolaus, Marcel (In: Anhaus, P et al. (2025): Spectral solar radiation over and under sea ice during the MOSAiC expedition 2019/20, version 2.0 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979856, 2025)
Transmitted solar radiance was measured using an ARC (Advanced-Radiance-Collector) RAMSES hyper-spectral radiometer (TriOS) mounted on the ROV during the MOSAiC expedition between November 2019 and September 2020 and normalized by the incident solar irradiance as measured using an ACC (Advanced-Cosine-Collector) RAMSES hyper-spectral radiometer (TriOS) installed on the sea ice. All times are given in Universal Coordinated Time (UTC).
Keywords: Arctic; BEAST; MOSAiC20192020; Remotely operated vehicle (ROV); Sea ice; Solar radiation